A nyolcosztályos népiskolai oktatás bevezetésének hatása az iskolalátogatással kapcsolatos szülői felügyeleti jogra - Niklai, Patrícia Dominika (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2019)
In connection with the implementation of the eight-grade elementary school system, questions were raised about the necessity of the work of children in the family and the need for compulsory education and the right of the child to education. The introduction of the eight-grade elementary school system was an important matter under the ministry of Kuno Klebelsberg, however, it was realized by Bálint Hóman, as a result of the Act XX of 1940 on schooling obligation and eight-grade elementary school. During the preparation of the Act, in 1939 Kálmán Kósa, the head of class of the ministry highlighted, that it is important to increase the duration of compulsory schooling, however, it should be kept in mind, that ’the adolescent children can continue to participate in the agricultural work, help their family with their work, when it is inevitably necessary to provide daily bread.’ Since the burden of parents would increase in the case of introducing eight-grade schooling, he urged to introduce two, a lower and a higher section in elementary school, so the students of the higher section would not go to school between April and October in order to help at home. The so called ‘Néptanítók Lapja’ (Teacher’s Journal) published the Act and its ministerial reasoning in 1940. Minister Hóman called it the most serious disability of the educational system that ‘the majority of our students finish their studies at their 12th age, which is the time, when they come to a dangerous and transient period of physical and psychological development.’ In my essay I will examine these two questions, highlighted by the Ministry of Culture as well, regarding the parents’ supervisory rights. On the one hand it is necessary to introduce eight-grade elementary schooling to educate children over the age of 12 properly, and on the other hand it is also important to limit the time of the eight-grade system, to ensure that the children can help at home. In order to find answers to these questions I will examine the provisions of the act, its ministerial reasoning and its welcome in the pedagogical press, and practical problems which led to the creation of the Act based on the documents of the National Archives of Hungary Baranya County Archives – such as the case of the thief band of the students of Pécs, as well as the reaction of the city to this band and the manifestation of the extraordinary effect of parental care. As it was written in many writings, it is also my aim to emphasize, that children’s behavior in this age was – and is nowadays – mostly effected by the family, so the success of introducing eight-grade schooling depends firstly on the relationship between the child and the parent, secondly on the relationship between the family and the school.